City-level meteorological conditions modify the relationships between exposure to multiple air pollutants and the risk of pediatric hand, foot, and mouth disease in the Sichuan Basin, China - Cai, Wennian; Luo, Caiying; Geng, Xiaoran; Zha, Yuanyi; Zhang, Tao; Zhang, Huadong; Yang, Changhong; Yin, Fei; Ma, Yue; Shui, Tiejun (Frontiers in Public Health, 2023)
Background: Several studies have examined the effects of city-level meteorological conditions on the associations between meteorological factors and hand, foot, and mouth disease (HFMD) risk. However, evidence that city-level meteorological conditions modify air pollutant-HFMD associations is lacking. For each of the 17 cities in the Sichuan Basin, we obtained estimates of the relationship between exposures to multiple air pollutants and childhood HFMD risk by using a unified distributed lag nonlinear model (DLNM). Multivariate metaregression models were used to identify the effects of city-level meteorological 2 conditions as effect modifiers. Finally, we conducted subgroup analyses of age and sex to explore whether the modification effects varied in different subgroups. The associations between PM2.5/CO/O3 and HFMD risk showed moderate or substantial heterogeneity among cities ( 2 statistics: 48.5%, 53.1%, and 61.1%). Temperature conditions significantly modified the PM2.5-HFMD association, while relative humidity and rainfall modified the O3-HFMD association. Low temperatures enhanced the protective effect of PM2.5 exposure against HFMD risk (PM2.5<32.7 µg/m³ or PM2.5>100 µg/m³, at the 99 th percentile: relative risk [RR]= 0.14, 95% CI: 0.03-0.60). Low relative humidity increased the adverse effect of O3 exposure on HFMD risk (O3>128.7 µg/m³, at the 99 th percentile: RR= 2.58, 95% CI: 1.48-4.50). However, high rainfall decreased the risk of HFMD due to O3 exposure (O3:14.1-41.4 µg/m³). In addition, the modification effects of temperature and relative humidity differed in the female and 3-5-year-old subgroups. Conclusions: Our findings revealed moderate or substantial heterogeneity in multiple air pollutant-HFMD relationships. Temperature, relative humidity, and rainfall modified the relationships between PM2.5 or O3 exposure and HFMD risk.